The Study of Thermal Conditions on Weibel Instability - M. Mahdavi; H. Khanzadeh (Advances in High Energy Physics)
Weibel electromagnetic instability has been studied analytically in relativistic plasma with high parallel temperature, where |α=(mc2/T∥)(1+p^⊥2/m2c2)1/2|≪1 and while the collision effects of electron-ion scattering have also been considered. According to these conditions, an analytical expression is derived for the growth rate of the Weibel instability for a limiting case of |ζ=α/2(ω′/ck)|≪1, where ω′ is the sum of the wave frequency of instability and the collision frequency of electrons with background ions. The results show that in the limiting condition α≪1 there is an unusual situation of the Weibel instability so that T∥≫T⊥, while in the classic Weibel instability T∥≪T⊥. The obtained results show that the growth rate of the Weibel instability will be decreased due to an increase in the number of collisions and a decrease in the anisotropic temperature by the increasing of plasma density, while the increase of the parameter γ^⊥=(1+p^⊥2/m2c2)1/2 leads to the increase of the Weibel instability growth rate.